2023
DOI: 10.2217/fvl-2022-0028
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Policies in Public Health to Address COVID-19 Vaccine Hesitancy

Abstract: A fundamental basis for effective health-related policymaking of any democratic nation should be open and transparent communication between a government and its citizens, including scientists and healthcare professionals, to foster a climate of trust, especially during the ongoing COVID-19 mass vaccination campaign. Since misinformation is a leading cause of vaccine hesitancy, open data sharing through an evidence-based approach may render the communication of health strategies developed by policymakers with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…The lack of vaccination campaigns and public health messaging to educate the populace on the significance of vaccination induces heightened public distrust, confusion, and skepticism. These findings are consistent with the findings of other scholars [ 11 , 23 , 40 ]. For instance, according to Johnson et al, educational campaigns about a disease-causing organism significantly improve people's attitudes toward vaccines.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The lack of vaccination campaigns and public health messaging to educate the populace on the significance of vaccination induces heightened public distrust, confusion, and skepticism. These findings are consistent with the findings of other scholars [ 11 , 23 , 40 ]. For instance, according to Johnson et al, educational campaigns about a disease-causing organism significantly improve people's attitudes toward vaccines.…”
Section: Discussionsupporting
confidence: 94%
“…For instance, according to Johnson et al, educational campaigns about a disease-causing organism significantly improve people's attitudes toward vaccines. Chirico and Da Silva reported that the lack of credible, transparent, and science-based information and recommendations results in mistrust in governments and the public health system, consequently lowering the will to be vaccinated [ 11 ]. A study by Viswanath et al reported a strong correlation between individuals' risk perceptions, namely, the severity of and susceptibility to COVID-19, and people's likelihood of receiving the vaccine [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Perspective piece in Philosophy of Medicine highlighted the importance of the robustness of evidence-based medicine, suggesting a transition in medicine based on empirical evidence to one based on "theory-oriented organismic systems" as a strategy to mitigate future pandemics (Marcum and Tretter 2023, 1). That suggestion complements another call for more rigorous scrutiny prior to the submission and publication of Covid-19 research, precisely so that the data available to healthcare workers is robust (Chirico and Teixeira da Silva 2023).…”
Section: The Current State Of Covid-19 Literature In a Nutshellmentioning
confidence: 93%
“…At the beginning of the pandemic, an alert was issued regarding the the risk of "quack" research (Freckelton 2020) being published in potentially predatory venues (Gupta et al 2020;Teixeira da Silva 2021a;Rebeaud et al 2022) and in explosive research volumes (Tiwari and Kaur 2020), risks that eventually manifested themselves in the form of misinformation, hyped treatments, solutions that were not supported by robust data (Kricorian, Civen, and Equils 2022), and an entire class of "research" (or that claimed to be research) that was stamped within popular circles and social media as "fake science," "fake news," or collectively conspiratorial information (Lee et al 2022), in part triggering vaccine hesitancy (Chirico and Teixeira da Silva 2023). At this juncture, it is best to note that not all venues that produce bad science are necessarily exploitative (that is, seeking to maximize benefit and/or profit off good research, as would be affirmed by the peerreviewed status of papers) or "predatory" (that is, seeking to maximize benefit and/or profit off bad research, as defined by the lack of peer review, combined with a business model built on exploiting authors' disingenuity).…”
Section: What Possible Reasons Might Explain the Existence Of Unrelia...mentioning
confidence: 99%
“…Studies have relied on real-time data sharing, open-access publications, and online platforms to disseminate findings promptly ( 139 ). Rapid dissemination of accurate information is crucial for guiding public health decision-making, enabling policymakers and healthcare professionals to implement evidence-based interventions, and fostering public trust and compliance with preventive measures ( 140 , 141 ).…”
Section: Introductionmentioning
confidence: 99%